2020
DOI: 10.7554/elife.56189
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic control of adipose tissue development and adult tissue homeostasis by platelet-derived growth factor receptor alpha

Abstract: Adipocytes arise from distinct progenitor populations during developmental and adult stages but little is known about how developmental progenitors differ from adult progenitors. Here, we investigate the role of platelet-derived growth factor receptor alpha (PDGFRα) in the divergent regulation of the two different adipose progenitor cells (APCs). Using in vivo adipose lineage tracking and deletion mouse models, we found that developmental PDGFRα+ cells are adipogenic and differentiated into mature adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 59 publications
(102 reference statements)
2
25
0
Order By: Relevance
“…Another group used PDGFRα-Cre-ER T2 mice generated by Rivers et al. [ 47 ] and showed that PDGFRα + APs did not participate in adult adipogenesis [ 48 ]. These studies were performed in different laboratories using different doses of TAM for recombination and with distinct Cre-drivers for producing transgenic models.…”
Section: Discussionmentioning
confidence: 99%
“…Another group used PDGFRα-Cre-ER T2 mice generated by Rivers et al. [ 47 ] and showed that PDGFRα + APs did not participate in adult adipogenesis [ 48 ]. These studies were performed in different laboratories using different doses of TAM for recombination and with distinct Cre-drivers for producing transgenic models.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, FGF13 inhibited myogenic differentiation of C2C12 myoblasts by activating ERK1/2 signaling [ 63 ]. Different from functions of the above genes in myogenesis, PDGFRα + mesenchymal progenitors were the major contributor to ectopic fat formation in skeletal muscle [ 37 ], and embryonic adipose progenitor cells without PDGFRα would undergo fate change from adipogenic to fibrotic lineage [ 64 ]. Although DNA methylation-induced PDGFRα and FGFR2 silencing has been reported in CG4 cells [ 65 ] or primary human pituitary adenomas [ 66 ], the role of DNA methylation in regulating the expression level of these co-different genes and their effects on myogenesis or adipogenesis still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we used platelet-derived growth factor receptor α (PDGFR-α) and α smooth muscle actin (α-SMA) antibodies to identify mesenchymal stromal cells that produce ECM and play important roles in wound healing of subcutaneous tissue of the skin 28 . PDGFR-α is a cell surface receptor tyrosine kinase expressed in mesenchymal stromal cells in a variety of tissues and is also used as a marker for adipose progenitor cells [29][30][31][32] . Immunohistochemical analysis indicated that PDGFR-α-positive cells were located along the panniculus carnosus layer in the wound region, and α-SMA-positive cells were located on the panniculus carnosus layer at the wound edge in Lepr db/+ mice.…”
Section: Resultsmentioning
confidence: 99%